Sosialisasi Sistem Filtrasi Sederhana Pada Budidaya Ikan Nila di Desa Cintakarya Kecamatan Parigi Kabupaten Pangandaran - Pietoyo, Atiek; Sofian , Achmad; Sudinno , Dinno; Prama , Ega Aditya; Astiyani , Wahyu Puji; Febriani , Vini Taru (Jaanur ElBarik Indonesia, 2025)
The Community Service activity in Karang Kamulyan Hamlet, Cintakarya Village, Pangandaran Regency, aimed to improve the knowledge of tilapia fish farmers about water quality management using a simple filtration system. River water sources contaminated by household waste are a crucial issue. Through a Community-Based Development (Comdev) approach and a learning-by-doing method, ten farmers were trained to construct mechanical filters using inexpensive local materials (gravel, charcoal, etc.). Evaluation showed increased knowledge about the risks and functions of filtration, and successfully created a solution that reduced operational costs and increased potential income. The main challenges were the optimal implementation of the three-mechanism filter (mechanical, chemical, biological) and limited land, which required further assistance